Numerical modelling of the opening process of the three-coating aortic valve - Kopernik, M.; Nowak, J. (Archives of Mechanics, 2009)
Numerical modelling of the three-coating human aortic valve is the objective of the paper. The proposed approach is used to select the material properties and the thickness of outer coating of the valve, which are required to obtain the proper work of the valve, which in the present paper is considered as the opening process. Following the previously developed model of the monocoating leaï¬‚et of the natural human aortic valve, the model of three-coating valve is prepared. Finite element method (FEM) and sensitivity analysis are used to solve the formulated and selected problems. Two methods of estimation of the valve opening process in numerical models are elaborated on the basis of experimental studies.